Vitamina C no soro e suco gástrico de pacientes dispépticos com e sem infecção por Helicobacter pylori - Silva, Carina Siqueira Martelli da (2015)
Introduction: Helicobater pylori interferes with vitamin C homeostasis and low levels of vitamin C may be a risk factor for H. pylori infection. Objective: to investigate the vitamin C serum and gastric juice levels of patients infected and non-infected by H. pylori. Additionally assess the association of vitamin C levels with H.pylori status, gastric pH and histological changes of gastric mucosa of dyspeptic patients with normal upper GI endoscopy. Methods: We studied 42 dyspeptic patients undergoing upper GI endoscopy had biopsies for diagnosis of H. pylori infection and gastric mucosa changes. We also collected 5 ml of blood (for dosage of serum vitamin C) and 10 ml of gastric juice. We measure pH of gastric juice. We used high-performance liquid chromatography to assess Vitamin C in serum and gastric juice. Results: The average age was 52 years (SD±11.8), 84.4% female, overweight BMI median 27,7) with adequate dietary intake of vitamin C. Twenty four (53.3%) patients had H. pylori infection. The median serum vitamin C levels in infected and non-infected was 3.9 and 3.4 μg (p = 0.59). The median gastric juice levels of vitamin C was 9,8 μg in infected and 18.4 μg in non-infected (p = 0.03). The histology showed normal mucosa in eight 8 (20%), chronic non-atrophic gastritis in 23 (55%) and chronic atrophic gastritis in 11 (26%) patients. There was no significant association of histology with Vitamin C serum levels (p = 0.26) or gastric (p = 0.29). Conclusion: Vitamin C serum levels were within the normal range, and most patients had adequate food ingestion of vitamin C. Serum levels of vitamin C were similar in individuals infected and non-infected while vitamin C levels in the gastric juice of patients infected were reduced compared with patients non-infected. Serum levels of vitamin C were higher in the gastric juice than in serum, regardless the patients were infected or not.